Why Monogamy? A Review of Potential Ultimate Drivers - Klug, Hope (Frontiers in Ecology and Evolution, 2018)
The existence of monogamy in animals is perplexing from an evolutionary perspective. If individuals: 1) have the opportunity to mate with more than one individual and 2) doing so provides fitness benefits (e.g., indirect benefits, increased mating success or fecundity), why does monogamy ever occur in animals? To address this question, we must examine how the potential benefits and costs of monogamy differ between the sexes and how such costs and benefits interact with factors including resource availability, offspring need, parental care, and mating dynamics (i.e., the costs and benefits associated with acquiring mates and mate availability). In this review, I examine the interplay between parental and offspring dynamics, resource availability and mate distribution, and mating dynamics. In doing so, I highlight the life history and ecological conditions under which monogamy is expected versus not. I then discuss areas of research that are needed to enhance our evolutionary understanding of monogamy. In particular, enhanced understanding of monogamy will come from: 1) more explicit consideration that the factors that lead to the origin of monogamy versus the maintenance of monogamy might differ and 2) identifying how potential interactions among factors influence the origin and/or maintenance of monogamy.